2016
DOI: 10.1002/cplu.201600075
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of 1,2‐Dicarbonyl‐3‐enes by Hydroacylation of 1‐Alkynes with Glyoxal Derivatives Using Metal–Organic Framework Cu/MOF‐74 as Heterogeneous Catalyst

Abstract: A crystalline copper‐based metal–organic framework Cu/MOF‐74 was synthesized, and used as an efficient heterogeneous catalyst for the synthesis of 1,2‐dicarbonyl‐3‐enes by means of the hydroacylation of 1‐alkynes with glyoxal derivatives in the presence of a base. Cu/MOF‐74 was found to be more catalytically active for the synthesis of 1,2‐dicarbonyl‐3‐enes than other MOFs including Cu2(BDC)2(DABCO), Cu3(BTC)2, Cu(BDC), Cu2(NDC)2(DABCO), Cu4I4(DABCO)2, Ni‐MOF‐74, Zn‐MOF‐74, Fe3O(BDC)3, In(OH)(BDC), and Zr6O4(O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…The broad peak in the range 3000–3650 cm –1 was assigned to the hydrogen bonds of the free hydroxyl groups. The strong bands at 1641 and 1423 cm –1 were assigned to the stretching vibration of the −COOH bond, which confirmed the presence of H 4 dhtp ligands in the framework. The bands at 698 cm –1 were related to the stretching and plane bending vibrations of the benzene ring.…”
Section: Resultsmentioning
confidence: 70%
“…The broad peak in the range 3000–3650 cm –1 was assigned to the hydrogen bonds of the free hydroxyl groups. The strong bands at 1641 and 1423 cm –1 were assigned to the stretching vibration of the −COOH bond, which confirmed the presence of H 4 dhtp ligands in the framework. The bands at 698 cm –1 were related to the stretching and plane bending vibrations of the benzene ring.…”
Section: Resultsmentioning
confidence: 70%
“…Metal-organic frameworks (MOFs) have diversity of structures, [7][8][9] which have been widely applied in recent years. [10][11][12][13][14][15][16][17] Among different types of MOFs, excellent stability and specic structure endow luminescent MOFs the ability to detect metal ions (Cu 2+ , Fe 3+ ), explosives (nitrobenzene, 4-nitrophenol, TNT, and 2,4,6-trinitrophenol), and inorganic anions (NO 3…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the research teams of Phan and Truong reported the hydroacylation of terminal alkynes with glyoxalates using a Cu-MOF-74/base catalytic system at 100 °C for 4 h (Scheme 23). 84 Particularly, the performance of this MOF catalyst was found to be superior to that of the homogeneous copper salts and other MOFs (Ni-MOF-74, Zn-MOF-74, Fe 3 O(BDC) 3 , In(OH)(BDC), UiO-66, and a series of Cu-based MOFs). 84…”
Section: Mechanism and Behavior Of Porous Materials As Catalysts For ...mentioning
confidence: 91%
“…84 Particularly, the performance of this MOF catalyst was found to be superior to that of the homogeneous copper salts and other MOFs (Ni-MOF-74, Zn-MOF-74, Fe 3 O(BDC) 3 , In(OH)(BDC), UiO-66, and a series of Cu-based MOFs). 84…”
Section: Mechanism and Behavior Of Porous Materials As Catalysts For ...mentioning
confidence: 91%